Integrating psychotherapy and psychopharmacology: psychedelic-assisted psychotherapy and other combined treatments. Issue 6 (2nd June 2020) - Greenway, Kyle T.; Garel, Nicolas; Jerome, Lisa; Feduccia, Allison A.
ABSTRACT: Introduction: Combinations of psychotherapy with antidepressants are gold-standard psychiatric treatments. They operate through complex and interactional mechanisms, not unlike the reemergent paradigm of psychedelic-assisted psychotherapy, which promising research suggests may also be highly effective in even challenging populations. Areas covered: We review the therapeutic mechanisms behind both conventional and psychedelic paradigms, including the evolution of this knowledge and the associated explanatory frameworks. We explore how psychedelics have provided insights about psychiatric illnesses and treatments over the past decades. We discuss limitations to early explanatory models while highlighting and comparing the psychological and biological mechanisms underlying many psychiatric treatments. Methods: A narrative review was conducted based on a search in Medline/Pubmed up to January 1 st, 2020, and iterative retrieval of references from recent reviews and clinical trials. Expert opinion: The contextual model of the common factors of psychotherapy provides a powerful perspective on psychotherapy, antidepressants, and psychedelics, as well as 3, 4-methylenedioxymethamphetamine (MDMA) and ketamine. It aligns well with key tenets of psychedelic-assisted psychotherapy. Conventional antidepressants and especially psychedelics may improve the efficacy of psychotherapy via neurochemical changes and increased environmental sensitivity. Combined treatments hold significant promise for advancing the knowledge and treatment of many forms of psychopathology.